2019
DOI: 10.3727/096504018x15482423944678
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of Gleditsia sinensis Extract in Rats Transplanted With Hepatocellular Carcinoma Cells

Abstract: The thorns of Gleditsia sinensis have been historically used in Chinese medicine and are considered one of the fundamental therapeutic herbs. Its anticancer effects are currently being explored. Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer and still requires the development of new drugs with higher efficiency. By using a rat HCC model implanted with cancerous Walker-256 cells, the therapeutic effects of G. sinensis extract (GSE) were assessed, as well as its regulatory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…Claimed as an anticancer drug in the TCM system, the cytotoxic effects of Spina Gleditsiae have been reported in several in vitro and in vivo models. [3][4][5][6][7] However, the phytochemical foundation of the anticancer activities of Spina Gleditsiae still needed further elucidation. Previously, 3 compounds identified from Spina Gleditsiae were known to inhibit the growth of human SK-Hep-1 liver cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Claimed as an anticancer drug in the TCM system, the cytotoxic effects of Spina Gleditsiae have been reported in several in vitro and in vivo models. [3][4][5][6][7] However, the phytochemical foundation of the anticancer activities of Spina Gleditsiae still needed further elucidation. Previously, 3 compounds identified from Spina Gleditsiae were known to inhibit the growth of human SK-Hep-1 liver cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Its pharmacological effects were determined to be regulatory effects on miRNAs, including miR-21/181b/183. 3 In both in vitro and in vivo colon cancer HCT116 models, the ethanol extract of Spina Gleditsiae inhibited the growth of cancer cells with an IC 50 at 600 μg/mL and significantly reduced tumor size in HCT116-xenografted tissues. These activities were associated with the regulation of expression of ERK phosphorylation, p27, and matrix metalloproteinase-9 (MMP-9).…”
mentioning
confidence: 99%
“…In addition, Gleditsia sinensis extract has been historically used in Chinese medicine and is considered one of the fundamental therapeutic herbs. The anti-breast cancer effect for Gleditsia sinensis probably results in upregulation of PDCD4 expression to promote cell apoptosis ( 84 , 85 ). Curcumin is a constituent of the yellow powder extracted from the roots of Curcuma longa Linn.…”
Section: The Regulators Of Pdcd4 In Breast Cancermentioning
confidence: 99%
“…Gleditsiae Spina, the thorn of G. sinensis , has been historically used as herbal medicine in East Asian countries, such as China, Korea and Japan (Gao et al, 2016). Pharmacological studies have revealed that Gleditsiae Spina has antioxidant, antibacterial, anti‐inflammatory and antitumor effects, and can effectively improve immunity (Cai et al, 2019; Lee et al, 2011, 2012; Li et al, 2018; Yi et al, 2015; Yoo et al, 2010; Yu et al, 2021). Flavonoids compounds are the major bioactive substances detect from Gleditsiae Spina, and they exhibit a wide range of biological activities, such as anticoagulant, antimicrobial, antiviral, antitumor, anti‐inflammatory and antidepressant effects (Hu et al, 2020; Li et al, 2010; Liu et al, 2021; Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%